Integration of GIS and HEC-RAS in Floods Modeling of Martil River (Northern Morocco) - Azouagh, Amina; El Bardai, Rabei; Hilal, Ismael.; Stitou el Messari, Jamal. (European Scientific Journal, ESJ, 2018)
This work describes the application of Hec-RASas Hydrologic Engineering Center derived River Analysis System model to the establishmentof floodplain maps for Martil river. Modeling with Hec-Ras enables calculation of, among other variables, water levels, depths and flow velocities for the different flow configurations and different cross-sectional zones along Martil River, i. e., from the confluence with the Lakhmiss and Mhajrat rivers to discharge into the Mediterranean Sea. This investigation, therefore, presents flood mapping and classification of risk areas using the Hec-GeoRas and Hec-Ras hydraulic modelling tools integrated into the Arcgis information system. The results indicate that the use of aerial photographsprovidesa good knowledge of the morphology and physical characteristics of the river, which will help decision makers to prevent floodingin the urban area of Tetuan.